Local Government Budget Stabilization: Explorations and Evidence - Hou, Yilin (Springer, 2015)
This book is the first comprehensive, full-scale treatment of the politics, law, and economics with regard to the policies and policy instruments for budget stabilization at the local level. It examines budget stabilization in the United States from the 1910s to 2010 (from adoption of public budgeting in this country through the Great Recession). In addition, it provides details on the methods and results of empirical tests of the effects of budget stabilization instruments on government operations, key/basic services provision, and some other aspects of social and economic life at the local level, including full-purpose governments (county, metro city, municipality, township, and village) as well as special (single-) purpose governments (like school districts and transportation districts). This book dissects an important and pressing issue in public financial administration, analyzes a lesson that has been in the learning process, especially in the United States, and identifies theoretical threads for scholarly refinement, which will be put into specific contexts of policy design and implementation. This book will be of interest to scholars in political science, economics, public choice and in public administration, where it will also appeal to policy-makers.